2017
DOI: 10.1589/rika.32.221
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Young and Elderly Adults in a Standing-walking Task

Abstract: [Purpose] Young and elderly adults performed walking and standing-walking (ST) tasks, and the number of steps taken before achieving normal gait and the characteristics of transitional gait were investigated.[Subjects and Methods] The subjects were 19 elderly females and 10 healthy young females.Step length and gait speed were measured at the maximum gait in both tasks, and in the ST task, the anterior transfer speed of the center of gravity (COG) and motor function were also compared. [Results] In the walki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In the current study, three walking periods were set for each number of steps based on a previous study that showed that older adults walking generally became steady after the fourth step from the start of walking. 17 In the early period from the start of walking to the fourth step, walking was still unstable, which is consistent with the period when older adults are more likely to fall. On the other hand, it has been reported that walking becomes steady and stable in the mid-period, but the variance values and PtP were significantly different between +CD and −CD in all periods.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In the current study, three walking periods were set for each number of steps based on a previous study that showed that older adults walking generally became steady after the fourth step from the start of walking. 17 In the early period from the start of walking to the fourth step, walking was still unstable, which is consistent with the period when older adults are more likely to fall. On the other hand, it has been reported that walking becomes steady and stable in the mid-period, but the variance values and PtP were significantly different between +CD and −CD in all periods.…”
Section: Discussionsupporting
confidence: 70%
“…These combined with the results of this study suggest that wearing complete dentures during walking may contribute to the stability of both the trunk and head, but the effect on the head may be more significant. In the current study, three walking periods were set for each number of steps based on a previous study that showed that older adults walking generally became steady after the fourth step from the start of walking 17 . In the early period from the start of walking to the fourth step, walking was still unstable, which is consistent with the period when older adults are more likely to fall.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations